Perlindungan Hukum terhadap Transaksi E - Commerce dalam Transaksi Bisnis Internasional - Vannya Anastasya (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Information technology has driven the growth of global e-commerce, enabling rapid cross-border transactions. However, this situation has also raised a number of issues regarding legal protection, such as differences in legal systems between countries, conflicts of jurisdiction, inadequate consumer protection, and an increased risk of cybercrime. This study uses a normative legal approach, utilizing a literature review and a legislative approach. The study's findings show that legal protection for international e-commerce encompasses preventive elements (the ITE Law and UNCITRAL) and repressive elements (courts, arbitration, and ODR). However, due to the absence of harmonized international law and cross-border enforcement challenges, its effectiveness remains limited. Consequently, to create safe and sustainable e-commerce transactions, strengthening of regulations, digital security, and digital literacy is required.